Association of life style and dietary habits with blood choline and cardiovascular outcome - Ali, Muhammad Asif; Nasir, Muhammad; Pasha, Talat Naseer; Javid, Imran; Ullah, Azmat; Iqbal, Muhammad Amir; Ahmed, Sheraz; Nazir, Muhammad Mudasser; Gondal, Tanweer Aslam; Imran, Muhammad; Sharifi-Rad, Javad; Mahomoodally, Mohamad Fawzi (Cellular and Molecular Biology, 2020)
Whole-blood choline, plasma choline and serum choline are emerging biomarkers in cardiovascular diseases (CVD). To examine the association of Whole-blood choline is an early predictor for cardiac events. In case control study, we enrolled 240 individuals including 120 normal (39 females and 82 males) and 120 cases (49 females and 71 males) where age limit was >40 years) Information through interviews, family disease history, 24 recall diet assessment and blood sampling. Odds ratios express the associated risks with CVD and without CVD patients. In healthy populations, good dietary habits and active lifestyle were observed. The number of participants with CVD were smokers than normal. In men, and women the risk was observed highly significant. (p=0.0049) Different blood parameters like Triglycerides, Uric Acid, Urea, Creatinine, CRP and ESR were non-significant observed. In females the low carbohydrates and high protein and frequent salad vegetable consumption observed. On the other hand, men consume more carbohydrates. Body mass index was significantly with p= 0.036 (OD 1.12 95% 1.00-1.26). The total fats (p=0.017) (OD 1.3301 95% 1.05-1.69) total carbohydrate (p=0.076) (OD 1.1536 95% 0.98-1.35) and total proteins (p=0.287) (OD 1.1456 95% 0.89-1.47) effecting respectively. The Blood choline level was significant observed between cases (p=0.026) OD (0.944 95%0.89- 0.99).